Italy and Australia Redefining Bilateral Relations for the Twenty-First Century - Abbondanza, Gabriele; Battiston, Simone (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
"This book offers a rigorous and innovative appraisal of contemporary Italian-Australian relations. Among the many insights, its international relations implications are particularly valuable to understanding how bilateral ties can be further strengthened in the future." -Thomas Wilkins, Associate Professor, University of Sydney "This is a long-awaited analysis of current and future opportunities across Australian-Italian trajectories. Editors and contributors are to be commended for this compelling and transdisciplinary endeavour." -Alice Loda, Lecturer, University of Technology, Sydney This book offers a novel and comprehensive reappraisal of current relations between Italy and Australia. For the first time, it expands the scope of analysis by encompassing and critically reviewing research avenues that have been understudied so far. In order to pursue this objective, it provides innovative analyses on bilateral history, reciprocal migration, socio-cultural ties, international relations and trade, comparative politics, and scientific cooperation. By adopting a multidisciplinary approach, this book makes a significant contribution to multiple disciplinary literatures, benefitting social science scholars, policymakers, and professionals working in a number of fields. Mindful of the wide scope and multidisciplinary nature of this innovative research, the editors oversee a careful balance of different theories, methodologies, sources, and data, in accordance with the conventions of each discipline employed in this volume. As a result, this book encourages a broader and more nuanced understanding of Italian-Australian relations in the 21st century. Dr. Gabriele Abbondanza is Marie Curie Fellow at the Complutense University of Madrid (Spain); and Associate Researcher at both the University of Sydney (Australia) and the Italian Institute of International Affairs - IAI (Italy). His research focuses on Australian and Italian foreign policy; irregular migration; the Indo-Pacific; and middle power and great power theory. Dr. Simone Battiston is Senior Lecturer in history and politics at Swinburne University of Technology (Australia). His research examines different aspects of post-war Italian migration, with a particular attention to the Australian context: external voting behaviour, history and memory of radical migrants, and migrant media history.
Chapter 1 Italy and Australia in the twenty-first century: distant connections or close partners? -- Chapter 2 A historical overview of Italian-Australian bilateral relations -- Chapter 3 Italians in Australia in the twenty-first century -- Chapter 4 Australians in Italy in the twenty-first century -- Chapter 5 First Nations sovereignty: towards a decolonial approach to Italy-Australia relations -- Chapter 6 Connecting Australia and Italy through language -- Chapter 7 Time for a strategic partnership: the scope for international cooperation between Italy and Australia -- Chapter 8 The Australian interest in the European Union and the Italian interest in the Asia-Pacific -- Chapter 9 Twenty-first century populism in Australia and Italy: A comparative analysis -- Chapter 10 Italian-Australian Scientific and Research Cooperation -- Chapter 11 Where to from here? The need for a long-term strategy in Italian-Australian relations.
Keywords: International relations; Diplomacy; International Relations; Diplomacy